KONSEP PENDIDIKAN IMAM AL-GHAZALI DAN RELEVANSINYA DALAM SISTEM PENDIDIKAN DI INDONESIA - Nurohman (AS-SALAM, 2020)
Al-Ghazali is a great thinker and scholar with work in various fields of science such as religion, philosophy, Sufism, morals, politics, and others. The greatest work of Imam Al-Ghazali is the book of Ihya ?Ulum Ad-Din, where education according to Al-Ghazali is a process of activities carried out systematically to give birth to progressive changes in human behavior. In Al-Ghazali's view, central in education is the heart because the heart is the essence of humanity because human substance is not located in the physical elements, but resides in the heart and views humans as theocentric, so the concept of education is more directed at the formation of moral character. The concept of Al-Ghazali's education can be known by understanding his thoughts regarding various aspects related to education namely the objectives of education, curriculum, teacher and student ethics, and learning methods. The concept of education that was sparked by Imam Al-Ghazali is very relevant to the education system in Indonesia in terms of educational goals, the concept of educators and students, learning methods, and curriculum currently applied, especially character education, which at the application level is very prioritizing on aspects of development intellectual, moral, and spiritual so that they are able to develop the potential of students to become human beings who have faith and are devoted to God Almighty, have good character, are healthy, knowledgeable, capable, creative, independent, and become democratic and responsible citizens.